Lateglacial and early holocene environments and human occupation in Brandenburg, Eastern Germany - Kobe, Franziska; Bittner, Martin K.; Leipe, Christian; Hoelzmann, Philipp; Long, Tengwen; Wagner, Mayke; Zibulski, Romy; Tarasov, Pavel E. (Lomonosov Moscow State University, Faculty of Geography, 2019)
The paper reports on the results of the pollen, plant macrofossil and geochemical analyses and the AMS 14C-based chronology of the «Rüdersdorf» outcrop situated east of Berlin in Brandenburg (Germany). The postglacial landscape changed from an open one to generally forested by ca. 14 cal. kyr BP. Woody plants (mainly birch and pine) contributed up to 85% to the pollen assemblages ca. 13.4–12.5 cal. kyr BP. The subsequent Younger Dryas ( YD) interval is characterized by a decrease in arboreal pollen (AP) to 75% but led neither to substantial deforestation nor spread of tundra vegetation. This supports the concept that the YD cooling was mainly limited to the winter months, while summers remained comparably warm and allowed much broader (than initially believed) spread of cold-tolerant boreal trees. Further support for this theory comes from the fact that the relatively low AP values persisted until ca. 10.6 cal. kyr BP, when the «hazel phase» of the regional vegetation succession began. The postglacial hunter-gatherer occupation is archaeologically confirmed in Brandenburg since ca. 13 cal. kyr BP, i.e. much later than in the western part of Germany and ca. 1000 years after the major amelioration in the Rüdersdorf environmental record.